Thermoregulatory, Tibia Bone Geometry and Calcium Indices of Heat-Stressed Broiler Chickens Fed Toasted Sorrel Seed Meal - Ademu, L. A; Daudu, O. M.; Jibrin, N.; Mohammed, F. (Nigerian Journal of Animal Science and Technology (NJAST), 2021)
An experiment was conducted to investigate the effect of dietary inclusions of Toasted Sorrel Seed Meal (TSSM) on the thermoregulatory, tibia bone geometry and calcium indices of heat-stressed broiler chickens. One hundred and thirty-five day old broiler chicks were randomly allotted to three experimental treatments. Each treatment was replicated three times with fifteen birds per replicate in a completely randomized design. TSSM replaced soya bean meal at graded levels of 0, 10 and 20 %. Results indicated that Temperature Humidity Index (THI) in the afternoons was higher than THI in the morning by 12.52 %, indicating the presence of heat stress at both periods of the day. Rectal temperature and respiratory rate decreased (P>0.05) with increasing levels of TSSM. Results for faecal calcium was significant (P<0.05) indicating a reduction in faecal calcium in the TSSM groups. Bone calcium levels was also significant (P<0.05). All bone geometric properties considered were not significant (P>0.05). TSSM had positive effects on thermoregulatory and calcium indices especially on faecal calcium in broiler chickens. It was concluded that TSSM up to 20 % inclusion positively affected respiratory rate and rectal temperature while significantly reducing urinary calcium levels.